A novel holistic framework for genetic‐based captive‐breeding and reintroduction programs. Issue 5 (9th May 2016) - Attard, C.R.M.; Möller, L.M.; Sasaki, M.; Hammer, M.P.; Bice, C.M.; Brauer, C.J.; Carvalho, D.C.; Harris, J.O.; Beheregaray, L.B.
Abstract: Research in reintroduction biology has provided a greater understanding of the often limited success of species reintroductions and highlighted the need for scientifically rigorous approaches in reintroduction programs. We examined the recent genetic‐based captive‐breeding and reintroduction literature to showcase the underuse of the genetic data gathered. We devised a framework that takes full advantage of the genetic data through assessment of the genetic makeup of populations before (past component of the framework), during (present component), and after (future component) captive‐breeding and reintroduction events to understand their conservation potential and maximize their success. We empirically applied our framework to two small fishes: Yarra pygmy perch (Nannoperca obscura) and southern pygmy perch (Nannoperca australis). Each of these species has a locally adapted and geographically isolated lineage that is endemic to the highly threatened lower Murray–Darling Basin in Australia. These two populations were rescued during Australia's recent decade‐long Millennium Drought, when their persistence became entirely dependent on captive‐breeding and subsequent reintroduction efforts. Using historical demographic analyses, we found differences and similarities between the species in the genetic impacts of past natural and anthropogenic events that occurred in situ, such as European settlement (past component). Subsequently, successful maintenance of genetic diversity in captivity—despite skewed brooder contribution to offspring—was achieved through carefully managed genetic‐based breeding (present component). Finally, genetic monitoring revealed the survival and recruitment of released captive‐bred offspring in the wild (future component). Our holistic framework often requires no additional data collection to that typically gathered in genetic‐based breeding programs, is applicable to a wide range of species, advances the genetic considerations of reintroduction programs, and is expected to improve with the use of next‐generation sequencing technology.